Overexpression of Plasmodium falciparum M1 Aminopeptidase Promotes an Increase in Intracellular Proteolysis and Modifies the Asexual Erythrocytic Cycle Development - Carolina C. Hoff (MDPI AG, 2021)
Plasmodium falciparum, the most virulent of the human malaria parasite, is responsible for high mortality rates worldwide. We studied the M1 alanyl-aminopeptidase of this protozoan (PfA-M1), which is involved in the final stages of hemoglobin cleavage, an essential process for parasite survival. Aiming to help in the rational development of drugs against this target, we developed a new strain of P. falciparum overexpressing PfA-M1 without the signal peptide (overPfA-M1). The overPfA-M1 parasites showed a 2.5-fold increase in proteolytic activity toward the fluorogenic substrate alanyl-7-amido-4-methylcoumarin, in relation to the wild-type group. Inhibition studies showed that overPfA-M1 presented a lower sensitivity against the metalloaminopeptidase inhibitor bestatin and to other recombinant PfA-M1 inhibitors, in comparison with the wild-type strain, indicating that PfA-M1 is a target for the in vitro antimalarial activity of these compounds. Moreover, overPfA-M1 parasites present a decreased in vitro growth, showing a reduced number of merozoites per schizont, and also a decrease in the iRBC area occupied by the parasite in trophozoite and schizont forms when compared to the controls. Interestingly, the transgenic parasite displays an increase in the aminopeptidase activity toward Met-, Ala-, Leu- and Arg-7-amido-4-methylcoumarin. We also investigated the potential role of calmodulin and cysteine proteases in PfA-M1 activity. Taken together, our data show that the overexpression of PfA-M1 in the parasite cytosol can be a suitable tool for the screening of antimalarials in specific high-throughput assays and may be used for the identification of intracellular molecular partners that modulate their activity in P. falciparum.